Integrating Molecular, Digital, and Morphological Insights: The Unavoidable Future of Oncologic Diagnostics - Hasibuan, Arie Widiansyah; Delyuzar, Delyuzar (Indonesian Journal of Cancer, 2026)
The remarkable progress of Anatomical Pathology over recent decades has fundamentally reshaped the landscape of oncologic diagnostics. From the early era when microscopic interpretation of routine hematoxylin-eosin (HE) stained sections formed the diagnostic cornerstone, the discipline has evolved into a complex hub of integrated biological data. This journey began with mastery of histopathological and cytological morphology and expanded to the use of histochemical and immunohistochemical stains, enabling precise visualization of specific proteins. The transformation continued as molecular technologies became routinely implemented in major laboratories, extending diagnostic capacity far beyond the limits of the optical microscope [1]. Advances in molecular techniques have opened a new dimension in cancer understanding. Polymerase chain reaction (PCR), real-time quantitative PCR, and reverse transcription PCR enable highly sensitive detection of gene mutations or transcripts, including EGFR mutations in pulmonary adenocarcinoma and BCR-ABL fusion transcripts in leukemia. Fluorescence in situ hybridization (FISH) adds the ability to visualize gene amplification or chromosomal rearrangements directly within cell nuclei, for example, to confirm HER2 amplification in breast carcinoma or ALK rearrangements in lung carcinoma. The most dramatic leap has come with next-generation sequencing (NGS), which uses massively parallel sequencing. It can interrogate hundreds to thousands of genes simultaneously. Targeted gene panels, whole-exome sequencing, and even whole-genome sequencing facilitate identification of driver mutations, copy number variations, and gene fusions in a single analysis. Tumor mutational burden and microsatellite instability status have now been recognized as critical biomarkers in selecting patients for immunotherapy. Moreover, transcriptomics, proteomics, and metabolomics, collectively referred to as “omics”, provide comprehensive insight into the interplay of genes, proteins, and metabolites that govern tumor biology and allow detection of germline mutations for familial risk assessment. The emergence of liquid biopsy, through analysis of circulating tumor DNA (ctDNA) and circulating tumor cells (CTCs), adds the ability to dynamically monitor the development of resistance mutations and therapeutic response without invasive procedures [1,2]. At the same time, digital technologies and artificial intelligence (AI) are revolutionizing the practice of pathology. Digital pathology using whole slide imaging (WSI) replaces glass slides with high-resolution digital files that can be stored, shared, and algorithmically analyzed. Deep-learning algorithms are now capable of highlighting tumor areas, quantifying proliferation indices such as Ki-67, and even predicting genetic mutations directly from HE images. Integration of AI not only accelerates diagnosis and reduces interobserver variability but also transforms histomorphologic images into quantitative data that can be correlated with clinical outcomes. These developments reposition the pathologist from a mere “slide reader” to an integrator of biological information combining morphology, molecular data, and digital analytics [2–5,7]. Despite the force of these innovations, morphology remains an irreplaceable foundation. Evaluation of tissue architecture in histopathology and cytology, and the recognition of growth patterns, continue to provide essential biological context that cannot be fully supplanted by genomic data. Histologic grading systems such as Nottingham for breast carcinoma and Gleason for prostate carcinoma remain critical determinants of risk stratification and therapeutic planning. Assessment of surgical margins, selection of representative tumor areas for further molecular analysis, and correlation with radiologic findings require the pathologist’s expertise as curator of tissue. Without quality control anchored in microscopic evaluation, molecular results risk being misleading [1]. Thus, the prediction that “pathologists will abandon the microscope” is only literally true because optical devices may be replaced by WSI monitors. It does not signify abandonment of morphological analysis itself [3–5]. This paradigm shift carries broad implications for every branch of oncology. Medical oncologists rely on molecular findings to guide targeted therapy; surgeons require accurate information to determine resection margins; and genetic counselors assess familial risk based on germline alterations. The concept of “integrated diagnosis” emphasized in the 5th edition of the World Health Organization classification of tumors provides the modern framework: the final diagnosis synthesizes morphology, immunohistochemistry, and molecular data into a single comprehensive report [1]. Contemporary cancer therapy decisions from the selection of tyrosine kinase inhibitors to checkpoint inhibitor immunotherapy can only be reached through such multidimensional interpretation [2]. Adoption of these advanced technologies demands robust infrastructure, significant financial investment, and personnel with bioinformatics expertise. Disparities between major referral centers and regional hospitals must be addressed so that progress does not widen gaps in cancer care. Issues of genomic data privacy, clinical validation of analytic pipelines, and legal responsibility for AI-assisted decisions require careful attention. Governments, educational institutions, and hospitals must invest in molecular pathology and bioinformatics curricula and prepare appropriate regulatory frameworks [7]. Anatomical Pathology is now entering an era in which the role of the pathologist has shifted from mere microscopic examiner to architect of integrated cancer biology data. The strengths of NGS, FISH, advanced PCR, omics, and liquid biopsy have opened new perspectives on cancer pathogenesis, precision therapy, and dynamic disease monitoring. Yet these advances do not diminish the role of morphology; rather, they reinforce its status as the foundation upon which molecular analysis and AI applications depend [1-5,7]. All oncology stakeholders must work together to build infrastructure and collaborative networks so that cancer services in Indonesia are fully prepared for the era of precision diagnostics, where molecular, digital, and morphological integration becomes the gold standard of modern cancer management.